Modeling of temperature variations in MOSFET mismatch for circuit simulations - Ismail, Muhamad Amri (Institute of Electrical and Electronics Engineers, 2009)
Temperature effect is one of the critical factors in manufacturing variability which could affect the designed circuit. This paper presents a MOSFET mismatch model with the consideration of temperature variations using physical based SPICE model parameters. The model development includes the mismatch measurement at different temperatures and enhancement of standard device model card. Mismatch temperature coefficients with respect to threshold voltage and carrier mobility are used to improve the prediction of mismatch model. The comparison between measured and Monte Carlo simulated data is presented for the verification purpose. The model is applied into the circuit design example to show the significant of the extracted mismatch temperature coefficients.